Solve for the indicated variable.

s = p + g/h for g.

2 Answer

  • Answer:

    g = h(s-p)

    Step-by-step explanation:

    1. find the variable of interest — It is in the numerator of one of two terms on the right side of the equation
    2. subtract every term on that side not containing the variable — subtract p to get s-p = g/h
    3. multiply by the inverse of the coefficient of the variable of interest — the coefficient is 1/h, so we multiply by h to get ... h(s-p) = g
    4. rearrange to the desired form. Here, it is probably OK to leave the parentheses and to simply put g on the left

    g = h(s -p)

  • Answer:

    (s-p)*h =g

    Step-by-step explanation:

    s = p + g/h

    Subtract p from each side

    s-p = p=p + g/h

    s-p = g/h

    Multiply by h

    (s-p) *h =g/h *h

    (s-p)*h =g